Predatory Publishing: A Medical Student Author's Perspective - Diego Arriaga Izabal (University Library System, University of Pittsburgh, 2024)
Predatory publishers are, generally, dishonest, lack transparency and center in publishing counterfeit journals to exploit the open-access model in which the author pays, and through this, obtain their self-interest profits. Unfortunately, these types of journals are on the rise and may easily deceive inexperienced researchers such as medical students who aspire to venture into research. In this context, the purpose of the present work is to offer a generalized view of 'predatory' magazines, how to identify them and avoid them; as well as raise awareness about its existence and discern its deceptive emails through my personal experience.